2019
DOI: 10.1186/s12884-019-2360-1
|View full text |Cite
|
Sign up to set email alerts
|

Serological screening of immunoglobulin M and immunoglobulin G during pregnancy for predicting congenital cytomegalovirus infection

Abstract: Background Cytomegalovirus (CMV) is one of the most frequent pathogens for congenital infections. Most cases of congenital CMV infection (cCMV) are asymptomatic at birth, but sensorineural hearing loss (SNHL) or neurodevelopmental delay can appear later in childhood. This prospective study examined the practicability of serological screening for anti-CMV immunoglobulin (Ig) G and anti-CMV IgM in pregnant women. Methods A total of 11,753 pregnant women were examined for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 35 publications
(38 reference statements)
1
38
2
3
Order By: Relevance
“…A previous study performed in pregnant Korean women reported rates of CMV IgG+/IgM+1.3% and CMV IgG+/IgM grey zone 0.4% comparable to the present study 7 . A previous study performed in pregnant Japanese women reported IgG+/IgM+ (4.3%), IgG‐/IgM+ (0.2%) and IgG+/IgM grey zone (1.2%), rates about two times higher than those of the present study 14 …”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…A previous study performed in pregnant Korean women reported rates of CMV IgG+/IgM+1.3% and CMV IgG+/IgM grey zone 0.4% comparable to the present study 7 . A previous study performed in pregnant Japanese women reported IgG+/IgM+ (4.3%), IgG‐/IgM+ (0.2%) and IgG+/IgM grey zone (1.2%), rates about two times higher than those of the present study 14 …”
Section: Discussionsupporting
confidence: 76%
“…7 A previous study performed in pregnant Japanese women reported IgG+/IgM+ (4.3%), IgG-/IgM+ (0.2%) and IgG+/IgM grey zone (1.2%), rates about two times higher than those of the present study. 14 Although there was no significant difference between annual number of congenital CMV infection and CMV IgG or IgM results in this study, the number of congenital CMV infections was more than five to 10 times higher than that of congenital rubella infection, with fewer than 10 annual cases under nationwide disease control with an immunization programme. 6 However, the efficacy of a national health screening programme for CMV infection still needs to be investigated.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…However, the negative to IgM antibody was observed in 15 CMV infections with dynamic increase for IgG level. The findings also demonstrate the opinion that the IgM result of a single serologic test is difficult and inconclusive to the diagnosis of TORCH infections [5, 21, 22].…”
Section: Discussionmentioning
confidence: 62%
“…A humorális immunválasz vizsgálatára, szerológiai diagnózis felállítására alkalmas érzékeny módszer az enzimhez kötött immunadszorpciós vizsgálat (ELISA; enzyme-linked-immunosorbent assay), további lehetőségek még az indirekt immunfluoreszcencián alapuló eljárások, western-blot, line immonoassay. A szerológiai vizsgálatokhoz jelenleg a kereskedelmi forgalomból beszerezhető ELISA készletek specificitása és szenzitivitása igen változó (5,11). Recombináns antigének és CMV peptid-fragmentek használata javíthatja a specificitást.…”
Section: Táblázatunclassified